Community of practice for open education [electronic resource] (Community College Consortium for Open Educational Resources (CCCOER), a division of Open Education Global (OEG), 2020)
CCCOER is a growing consortium of community and technical colleges committed to expanding access to education and increasing student success through adoption of open educational policy, practices, and resources. The Consoritum provides a community and resources to learn about the evolving practice of open education.